Globalization and development : (Kluwer Academic Publishers, 2004)
This book is a collective effort by researchers affiliated with the CERES Research School in Development Studies in the Netherlands. These experts discuss themes and concepts crucial to the overlapping fields of globalization and development research. Individual chapters examine the notions and issues of globalization, livelihood, identity, governance, transnationalism, and knowledge.